The Traits of Approval: Leadership Trait Theory Analysis as a Predictor of American Presidential Approval Ratings - Bronson, Emily Paige (My University, 2025)
This honors thesis is a project that shows statistical significance between leadership traits of American presidents and their approval ratings in a time-series like project. This project takes seemingly subjective leadership traits and assigns them numeric meaning using Leadership Trait Analysis piloted by Margaret Herman's scholarship. It required a new codebook and leadership analysis research model that the author of this project created, which can be further used to better presidential, federal, state and municipal candidacy.
Keywords: Presidential, Leadership, Traits, Approval Ratings, Quantitative.